The G20: Characters in search of an author - Ignazio Angeloni; Jean Pisani-Ferry (Bruegel, 2012)
The G20 has produced mixed results. After initial high hopes and some success, negotiations within the G20 forum have slowed, progress is less visible and disagreement rather than agreement has come to the fore. Against this background, this paper revisits the basic economic and geopolitical motivations for the G20, in order to review its performance and attempt to draw lessons for the path ahead. We conclude that: (1) in today's global economy (with its trade and financial market integration and its institutional architecture) a 'G20-type' institution is necessary - if it didn't exist, it should be created; (2) the G20 had its high noon moment in 2008-09 and some recalibration of expectations was inevitable, but its achievements in 2010-11 have nevertheless been disappointing; (3) to be fair there is, in detailed and technical work, more progress than there seems to be at first sight; (4) from a governance standpoint, the G20 is not an efficient forum; improvements in working methods are urgently needed; (5) more fundamentally, for the G20 to retain its role, its members need to develop a common vision of global economic problems and the way to approach them.
Keywords: 330; Internationale Wirtschaftspolitik; Internationale Wirtschaftspolitik; Global Governance; Bewertung; G-20-Staaten